Effects of Socio-Demographic Characteristics of Rural-urban Migrants in Plateau State: Path Model Approach - Yohanna Gwanshak, Joshua; Mohd Yusoff, Mariney Binti Mohd Yusoff; Shafie, Aziz Bin (IJRDO - Journal of Social Science and Humanities Research, 2020)
Migration is a complex phenomenon with the multiplicity of economic, social and security affecting migrants in their place of relocation. This shift has effects on migrants’ socio-demographic feature about the reason for rural to urban migration. The purpose of this study is to evaluate the direct effects of the socio-demographic status of migrants in Plateau State using variables of socio-demographic information and deriving factors of demography variable. The study uses stratified and purposive sampling techniques to administered 400 questionnaires to six (6) selected Local Government Area in the study area, of which 385 were retrieved successfully.  A path model analysis was utilized to evaluate the direct effects of the socio-demographic features of migrants and the result revealed a strong significance among the ten variables against reasons for migrants’ movement at both 95% and 99% confidence level. Job secured and occasional movement has direct effects on migrants of the socio-demography of migrants.